The wild plants used as traditional medicines by indigenous people of Manokwari, West Papua - OBED ï€ LENSE (Society for Indonesian Biodiversity, 2012)
Lense O. 2012. The wild plants used as traditional medicines by indigenous people of Manokwari, West Papua. Biodiversitas 13: 98- 106. The aims of the research were to identify the main plant species which are used as traditional medicines by native people in Manokwari District, West Papua Province and also to describe the method of preparation and uses of some of the medicinal plants. This research was conducted in seven sub-districts, ie. Manokwari, Ransiki, Kebar, Wasior, Mimyambouw, Merdey and Anggi-Sururey sub- District. Information recorded including methods of diagnosis and treatment of diseases, tribal name of a plant they used for treating disease (s), part of the plant used, preparation and mode of application, and whether the plant is used alone or in combination with other plants. Results indicate that the indigenous people in Manokwari District have been using at least 99 plant species (93 genera and 59 families) as sources of medicines. Most of these traditional medicinal plants are commonly gathered from the local tropical rainforest communities. At least 40 kinds of sickness and injuries such as malaria, fever, and wounds can be treated by using traditional medicinal plants from Manokwari District. Research also found that all parts of plants used, but leaf extracts are the most common part of the plant used for treating medical condition.